PEMAHAMAN MAHASISWA UNIVERSITAS RIAU TERHADAP ASEAN COMMUNITY 2015 - T, Loviana Permatasari; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study will describe how an undestanding the student of Riau University about ASEAN Community 2015. ASEAN Community is an International Cooperation of Southeast Asia region which aims to improve the economy. The importance of student to know about ASEAN Community because many of the challenges to be faced, especially in employment.This study used a qualitative descriptive research method. This page is more subjective with use the information, especially for the personal,and then use the interview and give a questionnaire to the subject.This reaserch shows that an understanding of the student in University of Riau is still low based from result of questionnaire.Keywords : ASEAN, ASEAN Community